2008
DOI: 10.1007/s00415-008-6003-0
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of multiple sclerosis for the development and validation of novel therapies – potential and limitations

Abstract: Various types of experimental autoimmune encephalomyelitis (EAE) reflect some of the pathogenetic, clinical, and therapeutic features of the different forms of multiple sclerosis (MS), thereby, providing some, albeit limited, insight into the molecular and cellular basis of the human disease. Specific questions of MS therapy including the search for new therapeutic targets and strategies and their validation require investigations in different available EAE models. A survey is given of experimental therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 108 publications
0
53
0
4
Order By: Relevance
“…In these models clues can be found to identify initiating, perpetuating, and reversing events of intestinal fibrosis, thereby allowing the creation of conceptual pathophysiological frameworks. On the other hand, differences between animal and human biological responses cannot be dismissed (86), and precaution must be taken when results of experimental systems are translated into clinical practice (87). Although animal models will never fully reproduce the complexity of human diseases, they can investigate and compare early events vs. late events, and this may lead to the development of new pathophysiology-based therapies.…”
Section: Intestinal Fibrosis In Animal Models: the Experimental Approachmentioning
confidence: 99%
“…In these models clues can be found to identify initiating, perpetuating, and reversing events of intestinal fibrosis, thereby allowing the creation of conceptual pathophysiological frameworks. On the other hand, differences between animal and human biological responses cannot be dismissed (86), and precaution must be taken when results of experimental systems are translated into clinical practice (87). Although animal models will never fully reproduce the complexity of human diseases, they can investigate and compare early events vs. late events, and this may lead to the development of new pathophysiology-based therapies.…”
Section: Intestinal Fibrosis In Animal Models: the Experimental Approachmentioning
confidence: 99%
“…69 This study showed that rIL-1ra or rIL-10 when overexpressed within the CNS during the remission phase of disease by means of a LV vector, clearly reduced clinical symptoms during the relapse, supporting the role of locally produced pro-inflammatory cytokines, including IL-1, in the relapse phase of cr-EAE. Although we are aware of the limitations when extrapolating results obtained by viral vectormediated gene expression in animal models to the real human disease, as shown for other MS treatments 70,71 we consider the use of low immunogenic LV vectors expressing either IL-10 or IL-1ra of therapeutic interest to prevent relapses in human MS.…”
Section: Cellular Localization Of Gfp Ril-10 and Ril-1ra In Vivo Aftmentioning
confidence: 99%
“…The development of mouse models of the immunological aspects of MS has proven extremely valuable in identifying antigenic and cellular components important in demyelination (Furlan et al, 2009;Mix et al, 2008). The disease that develops in these models depends on the specific antigenic stimulation and the genetic background of the host animal (Baxter, 2007;Krishnamoorthy and Wekerle, 2009).…”
Section: Pathogenic Mouse Models Have Identified Immune Mediators Of Msmentioning
confidence: 99%